Identifying absences: incentive for legal deposit of contemporary independent Mexican publishers’ production in National Library of Mexico - Hurtado Tarazona, Alejandra (2024)
This article presents the results of a research whose main objective was to establish an overview of the production and characteristics of Mexican independent publishers of the 21st century that are not part of Nautilo's catalog of the National Library of Mexico (BNM), in order to propose strategies for incorporating those works into the library collection through legal deposit. There were studied records of 112 independent Mexican publishers, leading to the following findings: 1. 69% of the projects are missing from the BNM collection due to non-compliance of legal deposit. 2. Within that 69% that is not included in the BNM, 51% of the projects do not have ISBN registration in their works, which makes more difficult to identify their production to encourage compliance of the legal deposit. 3. Essential characteristics of these projects were analyzed by examining their editorial catalogs and websites to facilitate the identification of their production. From the analysis of these data, it is concluded that there is a significant bibliographic gap in the production of contemporary independent Mexican publishers in the BNM, especially of those with more experimental practices, and it is emphasized the importance of drawing up strategies that encourage the fulfillment of their legal deposit, taking into account the particular characteristics of this type of edition.